Going greener: Synthesis of fully biobased unsaturated polyesters for styrene crosslinked resins with enhanced thermomechanical properties - C. S. M. F. Costa; A. C. Fonseca; J. Moniz; M. Godinho; J. F. J. Coelho; A. C. Serra (eXPRESS Polymer Letters)
The main goal of this work was the development of fully biobased unsaturated polyesters (UPs) that upon crosslinking with unsaturated monomers (UM) could lead to greener unsaturated polyester resins (UPRs) with similar thermomechanical properties to commercial fossil based UPR. After the successful synthesis of the biobased UPs, those were crosslinked with styrene (Sty), the most commonly used monomer, and the influence of the chemical structure of the UPs on the thermomechanical characteristics of UPRs were evaluated. The properties were compared with those of a commercial resin (Resipur 9837©). The BioUPRs presented high gel contents and contact angles that are similar to the commercial resin. The thermomechanical properties were evaluated by dynamic mechanical thermal analysis (DMTA) and it was found that the UPR synthesized using propylene glycol (PG), succinic acid (SuAc) and itaconic acid (ItAc) presented very close thermomechanical properties compared to the commercial resin.